Analysis of Bio-Obtainable Endocrine Disrupting Metals in River Water and Sediment, Sewage Influent/Effluent, Sludge, Leachate, and Concentrated Leachate, in the Irish Midlands Shannon Catchment - Antoinette M. Reid; Concepta A. Brougham; Andrew M. Fogarty; James J. Roche (International Journal of Analytical Chemistry)
The application of an acid digestion and subsequent solid-phase extraction (SPE) procedure were implemented as preliminary treatments prior to quantifying the levels of potentially endocrine disrupting metals (EDMs) in a variety of solid and liquid matrices. These included (solid) river sediment, leachate sediment and sewage sludge and also (liquid) river water, landfill leachate, concentrated leachate, sewage influent, and sewage effluent, sampled in the Irish Midlands. The total concentrations of cobalt (Co), cadmium (Cd), copper (Cu), chromium (Cr), nickel (Ni), lead (Pb), zinc (Zn), and manganese (Mn), after extraction and preconcentration, were determined by atomic absorption spectroscopy (AAS). Mercury (Hg) in sediment and sludge was determined using cold-vapour atomic fluorescence spectroscopy (AFS). For sewage sludge maximum values (mg/kgdw) of 4700 Ni, 1642 Mn, 100.0 Cd, 3400 Zn, 36.70 Co, 750.0 Pb, 485.8 Cr, and 1003 Cu were determined whilst in leachate sediment, maximum values (mg/kgdw) of 32.10 Ni, 815.0 Mn, 32.78 Cd, 230.3 Zn, 26.73 Co, 3525 Pb, 124.9 Cr, and 50.13 Cu were found. Over several months, the data showed elevated levels in sewage influents, effluents, and sludges compared to a battery of adjacent river water samples and corresponding sediments. There was a definite trend for target values for sediments to be exceeded, while intervention values were only exceeded for cadmium. Overall the pattern in terms of concentration was sewage > leachate > river matrices. A nonparametric assessment of the effect of sewage treatment method on median metal levels in sludge revealed statistically significant differences at the 95% level of confidence for Co, Cr, and Hg and at the 90% level of confidence for Cd.